Tolling Heavy Goods Vehicles on European Roads. From a Diverse Set of Solutions to Interoperability? - Viegas, José (European Journal of Transport and Infrastructure Research, 2003)
This paper is based on work carried out in the DESIRE research project of the European Commission’s 5th Framework Program, dedicated to the identification of preferred schemes for inter-urban tolling of Heavy Goods Vehicles (HGV’s) in the EU. As such, it presents some of the current developments related to this type of tolling, starting with the relevant transport policy background and a brief review of the various forms of tolling in existence and the main technological approaches used for tolling operations. A variety of situations in different countries studied in the project is then reviewed and presented in a framework that tries to put them in perspective according to several angles, accompanied by some explanation of the choices made in the various countries. A synthesis of this complex set of realities is produced thereafter in the form of a suggestion for a preferred form of pricing scheme. Recognising that various background conditions have led to legitimately different choices, but also that interoperability of each vehicle across regional and national borders is a natural request in international freight transport, the issue of the real value and costs of interoperability is finally discussed. It is argued that political difficulties for approval of these schemes at national level have been so strong that the policy package presented for parliamentary approval generally has to be very well tuned to the prevailing balances of power, thus leaving the issue of interoperability to a later stage. This evolution is currently of a relatively easy conceptual formulation, but many institutional and economic hurdles must be expected along the way. It is expected that interoperability may be reached within some 10 years, when there will be joint pressure for it from the demand side (hauliers) and from the supply side (technology suppliers).